Improvement Of Warehouse Management In A Muslim Fashion Company In Bandung City - Fadila Nurfauzia (SINTESA, 2022)
At this time Muslim fashion or what is more often called modest fashion, has begun to appear and become a trend. The target or market for Muslim fashion (modest fashion) has reached various circles, both Muslim and non-Muslim. One of the largest Muslim fashion companies in Indonesia is Elcorps. The elcorps group is a company that was founded in 2012. The elcorps group itself divides its business units into 4 industrial divisions, including the fashion industry, food industry, cosmetic industry, and tour and travel. One of the industries that is the biggest contributor to the company's revenue is the fashion industry. The brands in the fashion industry include Elzatta, Dauky, Zatta Men. In this Muslim fashion business activity, one of the important points is in the warehouse. But in this case, some problems come from the warehouse, including storage and product layout problems, to fulfilling orders for consumers. In this study using descriptive analysis research with qualitative methods, by collecting data using observation, interviews and documentation. Furthermore, the results of this study indicate that improvements must be made to warehouse management, one of which is storage management. The purpose of this study is to analyze and find out which activities or parts of warehouse management need to be improved. The advice recommended by the author is to make a stock control schedule or stock taking every 3 months on products that are in warehouse. improve the storage layout (storage) and improve the layout of the warehouse management.